تأثير وسائل الإعلام على الترابط الأسري دراسة ميدانية على عينة من الأسر بولاية أم البواقي - رحماني, مريم (جامعة الوادي - University of Eloued, 2021)
نحاول في هذ البحث تسليط الضوء على تعرض الطفل لوسائل الإعلام باعتباره الطرف الأكثر ضعفا وهشاشة وقابلية للتشكيل داخل الأسرة وانعكاساته على كيفية تواصله معهم ما يشخص الترابط الأسري القائم بينهم؛ و قد اعتمدنا في هذه الدراسة على المنهج المسحي وذلك باستخدام أداة الاستبيان عن طريق اختيار عينة عشوائية تكونت من 500 مفردة. وقد توصلت الدراسة إلى جملة من النتائج، أهمها أن وسائل الإعلام تؤثر في كيفية وحجم تواصل الطفل وتفاعله مع أفراد أسرته، حيث تشغل حيزا زمنيا كبيرا من حياته اليومية، ما يساهم بشكل تراكمي في التقليل من احتكاكه بأسرته، وهذا ما يزيد من التفكك الأسري بانغماسه في العزلة والانطوائية، ما يتيح لهذه الوسائل مجالا أفضل للتأثير عليه والسيطرة على أفكاره وسلوكاته . Abstract: In this research, we try to shed light on the child’s exposure to the media as the most vulnerable, fragile and vulnerable party within the family and its repercussions on how he communicates with them, which diagnoses the existing family bonding between them; In this study, we relied on the survey method, using the questionnaire tool, by selecting a random sample of 500 individuals. The study reached a number of results, the most important of which is that the media affect the way and the extent of the child’s communication and interaction with members of his family, as it occupies a large amount of time in his daily life, which cumulatively contributes to reducing his contact with his family, and this increases the family disintegration by immersing him in Isolation and introversion, which gives these means a better opportunity to influence him and control his thoughts and behavior.
The Influence Of The Media On Family Bonding A Field Study On A Sample Of Families In The State Of Oum El Bouaghi
مقال
Keywords: ترابط أسري، طفل، تأثير، سائل الإعلام، تعرض; Media, Exposure, Communication, Children, Influence, Family Bonding.